Building Branding Power and Digital Marketing for Community Empowerment - Maghfiroh, Ayik; Pertiwi, Dhia Kusuma; Yanuardi, Faqih Agil; Wulaningrum, Pipit Nur; Utami, Rima Fatika Dian; Fitri, Fitri (Khidmatuna: Jurnal Pengabdian Masyarakat, 2024)
This study evaluates the effectiveness of an educational seminar on product branding and digital marketing conducted by students of Universitas Islam Negeri Walisongo Semarang in Desa Pucangrejo. Held on August 3, 2024, the seminar featured Bapak Misbakhul Arrezki, S.E., M.M. as the speaker, focusing on branding strategies and digital marketing. Using observation as the research method, this study examined participant interactions and reactions during the seminar. Observations revealed that MSME actors in Desa Pucangrejo have not fully utilized digital technology and still rely on traditional marketing methods. Nevertheless, participants' enthusiasm indicated a growing awareness of the importance of branding and digital marketing. The seminar has the potential to enhance MSME knowledge and skills, expected to improve competitiveness and expand market reach. The implementation of the seminar's content is anticipated to assist local MSMEs in becoming more competitive in the global market.